Pembiasaan Senam di Sekolah Dasar Dalam Mewujudkan Tujuan Ketiga dari Program Sustainable Development Goals (SDGs) - Pratiwi, Arum Febriliana; Nugraheni, Nursiwi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This article was created with the aim of collecting information regarding the implementation of the sustainable development goals (SDGs) program in elementary schools. Of the seventeen SDGs goals, there is one goal that covers good health and welfare, which is listed in the third goal. In schools, the third goal of the SDGs can be implemented through physical health habituation programs such as gymnastics. Through this library research-based literature review method, some valid information was obtained regarding schools that have implemented gymnastics as a medium that can have a positive impact on students' health. Apart from health, there are other positive impacts such as changes in attitudes and better learning behavior which indirectly create a quality learning process.